Effect of freeze-thaw cycles on mechanical performance of loess soil stabilized with nano magnesium oxide - Peng Hu; Shufeng Chen; Zhao Duan; Nian-qin Wang; Ye Hao; Xian Wang (PLoS ONE, 2025)
Construction in northwest China is generally packed with issues linked to loess soil with poor engineering properties and day-night and seasonal freeze-thaw (FT) actions. This study explored the potential benefits of nano-MgO (NM) as an innovative solution for improving mechanical properties of loess. To this end, a series of unconfined compression test (UCT) and nuclear magnetic resonance tests (NMRT) were conducted. Results showed that the unconfined compressive strength (UCS) exhibited an a “rise-fall” trend with the addition of NM. An optimum dosage of 2% NM is expected to bring about 71.9% and 143.5% strength gain for non-FT and FT samples, respectively. Meanwhile, the FT-induced strength reduction ratio decreased from 56.3% to 38.1% with NM content from 0 to 2%. These illustrated that NM can be very effective in improving mechanical performance and alleviating freeze-thaw damage. On the other hand, deformation modulus presented similar trends with UCS, while failure strain behaved in a reverse way. Accordingly, empirical models for UCS, as well as its relationships with modulus and failure strain, were established and validated by literature data. Furthermore, nuclear magnetic resonance tests revealed that adding NM could increase the proportion of bound water with intensive interaction, yielding improved performance and durability. This investigation shows that NM represents an alternative to cement for soil stabilization, and provides scientific support for the construction design in cold regions.